2019
DOI: 10.1007/s11442-019-1994-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical characteristics and controlling factors of natural water in the border areas of the Qinghai-Tibet Plateau

Abstract: The special geography and human environment of the Qinghai-Tibet Plateau has created the unique hydrochemical characteristics of the region's natural water, which has been preserved in a largely natural state. However, as the intensity of anthropogenic activities in the region has continued to increase, the water environment and hydrochemical characteristics of the Qinghai-Tibet Plateau have altered. In this study, water samples from the western, southern, and northeastern border areas of the Qinghai-Tibet Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Generally, the dissolution and weathering of carbonate rocks (calcite, dolomite, etc.) in natural water is the main source of Ca 2+ and HCO -3 [5,9,55], and the weathering of magnesium-bearing carbonate rocks also provide Mg 2+ in the river [55]. In this study, Ca 2+ , Mg 2+ , and HCO -3 showed a highly significant correlation (p < 0.01), which also proved that these ions mainly originated from the weathering of carbonate rocks [13,55].…”
Section: Main Ionic Components and Hydrochemical Typessupporting
confidence: 70%
See 2 more Smart Citations
“…Generally, the dissolution and weathering of carbonate rocks (calcite, dolomite, etc.) in natural water is the main source of Ca 2+ and HCO -3 [5,9,55], and the weathering of magnesium-bearing carbonate rocks also provide Mg 2+ in the river [55]. In this study, Ca 2+ , Mg 2+ , and HCO -3 showed a highly significant correlation (p < 0.01), which also proved that these ions mainly originated from the weathering of carbonate rocks [13,55].…”
Section: Main Ionic Components and Hydrochemical Typessupporting
confidence: 70%
“…and the weathering of magnesium-bearing carbonate rocks also provide Mg 2+ in the river [55]. In this study, Ca 2+ , Mg 2+ , and HCO 3 showed a highly significant correlation (p < 0.01), which also proved that these ions mainly originated from the weathering of carbonate rocks [13,55].…”
Section: Main Ionic Components and Hydrochemical Typessupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, the above results demonstrated that the intense evaporation of groundwater, cation exchange, saltwater intrusion and human activity affected the groundwater (Cui and Li 2014;Li et al 2021;Xiao et al 2012). This region has the same hydrochemical type, evolution process and geochemical control factors of groundwater as the closed basin in the Qinghai-Tibet Plateau and arid area of northwest China (Li et al 2020;Tian et al 2019;Xiao et al 2018;Zhou et al 2021). The anions of groundwater tended to change from HCO 3 − to Cl − / SO 4 2−…”
Section: Factors Affecting Geochemical Characteristicsmentioning
confidence: 83%
“…For example, the exogenetic sulphuric acid and nitric acid generated by human activities accelerate the dissolution of carbonate rocks in the rivers ( Han & Liu, 2004 ; Li & Zhang, 2008 ; Li et al, 2010 , 2011b ; Ma et al, 2023 ), and therefore increases the concentrations of Ca 2+ , Mg 2+ , and HCO 3 − ; The average Cl − /Na + molar ratio of rivers is higher with more urbanized ( Tong et al, 2018 ), and The Cl – , Na + and K + are relatively high in rivers that significantly affected by municipal sewage discharge ( Qin et al, 2018 ); The application of agricultural fertilizer will significantly increase the K + , SO 4 2– , NO 3 – , and Cl – concentrations in the river water ( Etchanchu & Probst, 1988 ), and the SO 4 2– , Cl – , and Na + contents are relatively high in rivers on which industrial and mining wastewater have impacts ( Zhang et al, 2017 ). The intensification of human activities has led to a significant increase in the content of major ions in rivers, which has gradually become the dominant factor( Chen et al, 2020 ; Tian et al, 2019 ; Xu & Liu, 2007 ; Zeng et al, 2022 ; Zheng et al, 2022 ). Moreover, previous studies have shown that agricultural land and coal mines, municipal sewage, etc .…”
Section: Introductionmentioning
confidence: 99%